Direct Measurement of the Amount of Bound Collagen which Stimulates Platelet Aggregation - Kronick, Paul L; Jimenez, Sergio A (Thrombosis and Haemostasis, 1979)
The amount of collagen which binds to platelets has been correlated with aggregating activity in a platelet aggregometer. Aggregating activity requires only 0.22 μg/ml (0.35 μg/ 109 cells) of collagen bound, the reaction saturating with 4.9 μg/ml (7.9 μg/109 cells). On the basis of the fraction of collagen bound and its hydroxyproline/proline ratio, it is concluded that the activity resides in the type I collagen component.